Whole exome sequencing identifies a novel pathogenic variation [p.(Gly194valfs*7)] in SLC45A2 in the homozygous state in multiple members of a family with oculocutaneous albinism in southern India. (13th December 2019) - Lewis, S.S.; Girisha, K.M.
Summary: Deleterious mutations within the SLC45A2 gene, encoding membrane‐associated transporter protein (MATP), are responsible for type 4 oculocutaneous albinism. The cytogenetic location of SLC45A2 is 5p13.2 and it comprises seven exons located over around 40 kb. Its encoded protein, MATP, is 530 amino acids long and has 12 putative transmembrane domains. MATP is synthesized within melanocytes. It is in these cells that melanogenesis takes place and the melanin is contained within specialized organelles called melanosomes. Previous studies have shown that when MATP expression was reduced using small interfering RNA in MNT‐1 melanoma cells, pH was lowered within melanosomes, they became poorly melanized and tyrosinase activity within melanocytes was also reduced. This type of albinism produces a broad spectrum of phenotypes, ranging from complete absence of melanin to brown hair and brown irides. In the current study, blood was collected from a family in which four members had oculocutaneous albinism, showing a complete absence of melanin in skin, hair and eyes. Screening of the TYR gene using the extracted DNA showed no mutation and therefore whole exome sequencing analysis was performed. A novel deletion mutation c.579delG [p.(Gly194Valfs*7)] in the SLC45A2 gene, predicted to be pathogenic and to result in both frameshift and premature termination of the MATP chain, was identified. These data add to the information pertaining to the mutation spectrum of OCA4.